IMPLEMENTASI SENSOR FLEX PADA PENYANDANG DIFABEL MENGGUNAKAN DFPLAYER SEBAGAI INFORMASI AUDIO - Rasyid, Anas; Sollu, Tan Suryani; Indrajaya, Muhammad Aristo; Alamsyah, Alamsyah (Foristek, 2024)
Sign language is a form of language that can be learned which prioritizes communication with body language, facial expressions, and some non-sounds. This sign language is widely used by the deaf and mute. However, there is still a lack of institutions teaching sign language, books on sign language, and a tool for learning sign language. This study aims to design a hardware system that can translate sign language and output in the form of audio and display on the LCD. The stages of the research included designing the physical form of the device, testing the sensor flex, testing the MPU6050, testing the Nrf24l01, testing the Dfplayer, testing the Liquid Crystal Display (LCD), and testing the overall device on the A-Z alphabet. The results showed that when the Flex sensor was not indented the average error was 1.23%, and when it was indented the average error was 2.01%. The delay time required in sending data using Nrf24l01 media for conditions without obstructions is 0 seconds with a distance of 1 meter, with a barrier of 9.84 seconds with a distance of 3 meters, at a distance of 3 meters the data cannot be sent.